2021
DOI: 10.1590/0034-7167-2020-0773
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in care safety: Primary Health Care professionals’ perception

Abstract: Objectives: to analyze health professionals’ perception about the meaning and practice of patient involvement in care safety in Primary Health Care. Methods: this is an exploratory, qualitative study, developed with 22 professionals in the Federal District, Brazil. A semi-structured interview was conducted between October and November/2018. Content analysis was carried out according to Bardin. Results: nurses, physicians, dentists, among others, participated. The following categories emerged: Meaning of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
3
13
0
1
Order By: Relevance
“…The majority of studies suggested that it’s appropriate to expect patients to be accountable for their health-related behaviours [ 33 47 , 49 , 51 55 ] whether as a preventative strategy before the onset of disease [ 34 , 37 47 , 49 , 51 55 ], as a compliance strategy to minimize the health-related effects of disease [ 41 , 44 , 49 , 51 , 54 ], or as a responsible utilization strategy to minimize the waste of limited healthcare resources [ 48 , 51 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies suggested that it’s appropriate to expect patients to be accountable for their health-related behaviours [ 33 47 , 49 , 51 55 ] whether as a preventative strategy before the onset of disease [ 34 , 37 47 , 49 , 51 55 ], as a compliance strategy to minimize the health-related effects of disease [ 41 , 44 , 49 , 51 , 54 ], or as a responsible utilization strategy to minimize the waste of limited healthcare resources [ 48 , 51 , 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicated that individuals are accountable for lifestyle choices and risks that could have been avoided [ 33 , 34 , 37 39 , 41 – 43 , 47 , 48 , 56 ], attempting to make the best choices for their health [ 33 , 35 , 52 , 56 ] and implementing health promotion and healthy living and safe activities [ 49 , 51 ]. A study highlighted patient responsibilities, which included being truthful, providing a complete medical history, requesting information or clarification, complying with physician instructions, meeting financial obligations, being cognizant of the costs associated with healthcare, using medical resources judiciously and discussing the end of life decisions and organ donation [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 O termo "participação do paciente" pode ser definido como envolvimento do paciente no processo de tomada de decisão em relação às questões de saúde. 7 Partindo desse princípio, busca-se possibilitar que os pacientes tenham conhecimento sobre seu estado de saúde, sejam estimulados a interagir com os profissionais e participar das decisões do seu plano de cuidado. 8,9 Nessa perspectiva, a OMS criou a campanha "Patients for Patient Safety", com o objetivo de incluir os pacientes e acompanhantes na promoção da assistência segura e garantir que suas necessidades sejam respeitadas durante os cuidados de saúde.…”
Section: Introductionunclassified